Synthesis and Electrochemical Performance of Molybdenum Disulfide-Reduced Graphene Oxide-Polyaniline Ternary Composites for Supercapacitors - Bai, Li-Zhong; Wang, Yan-Hui; Cheng, Shuai-Shuai; Li, Fang; Zhang, Zhi-Yi; Liu, Ya-Qing (Frontiers in Chemistry, 2018)
Molybdenum disulfide/reduced graphene oxide/polyaniline ternary composites (MoS2/rGO/PANI) were designed and synthesized by a facile two-step approach including hydrothermal and in situ polymerization process. The MoS2/rGO/PANI composites presented an interconnected 3D network architecture, in which PANI uniformly coated the outer surface of the MoS2/rGO binary composite. The MoS2/rGO/PANI composites with a weight percent of 80% (MGP-80) exhibits the best specific capacitance (570 F g-1 at 1 A g-1) and cycling stabilities (78.6% retained capacitance after 500 cycles at 1 A g-1). The excellent electrochemical capacitive performance is attributed to its 3D network structure and the synergistic effects among the three components that make the composites obtain both pseudocapacitance and double-layer capacitance.